2015
DOI: 10.1002/aenm.201500400
|View full text |Cite
|
Sign up to set email alerts
|

Graphene‐Containing Nanomaterials for Lithium‐Ion Batteries

Abstract: Graphene‐containing nanomaterials have emerged as important candidates for electrode materials in lithium‐ion batteries (LIBs) due to their unique physical properties. In this review, a brief introduction to recent developments in graphene‐containing nanocomposite electrodes and their derivatives is provided. Subsequently, synthetic routes to nanoparticle/graphene composites and their electrochemical performance in LIBs are highlighted, and the current state‐of‐the‐art and most recent advances in the area of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
112
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 205 publications
(114 citation statements)
references
References 418 publications
(604 reference statements)
0
112
0
2
Order By: Relevance
“…After coating with outer layer carbon fiber, the double-layer carbon coating could limit the volume change of the whole electrode and the dissolution of metallic Mo and sulfides during the lithiation/delithiation cycles. Thus, even after long-term cycling, the MoS 2 /C/C fiber electrodes could still maintain the original fibrous network structure, which further explains why this double-layer carbon-coated MoS 2 material could display such an enhanced rate performance, high reversible capacity, and long-term cycle life [50].…”
Section: Resultsmentioning
confidence: 98%
“…After coating with outer layer carbon fiber, the double-layer carbon coating could limit the volume change of the whole electrode and the dissolution of metallic Mo and sulfides during the lithiation/delithiation cycles. Thus, even after long-term cycling, the MoS 2 /C/C fiber electrodes could still maintain the original fibrous network structure, which further explains why this double-layer carbon-coated MoS 2 material could display such an enhanced rate performance, high reversible capacity, and long-term cycle life [50].…”
Section: Resultsmentioning
confidence: 98%
“…Lithium ion batteries (LIBs) with both high power density and safety property are promising for applications in electric vehicles and large-scale energy storage stations [1][2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
“…The ability to enhance the specific capacity of LTO is of practical significance and offers the opportunity to broaden its use in high-power LIBs. It has been shown that widening the discharge cut-off voltage to 0 V is an effective way to increase the capacity of LTO at low 3 current density 13 . Two extra lithium ions can be further inserted into Li 7 Ti 5 O 12 to form Li 9 Ti 5 O 12 , accompanied by the reduction of all Ti 4+ to Ti 3+ in the compound.…”
Section: Introductionmentioning
confidence: 99%
“…A C C E P T E D ACCEPTED MANUSCRIPT 3 As an effective matrix to support electrochemically active materials in the electrode [16,17], graphene was logically introduced in the ternary Ge-based compounds to accommodate the volume change of Ge-based electrodes during cycling. In current literatures, hollow Zn 2 GeO 4 /rGO hybrids [18], sandwiched Zn 2 GeO 4 /graphene oxide [19], Zn 2 GeO 4 /N-Doped graphene [20], Zn 2 GeO 4 / graphene [21], Cd 2 Ge 2 O 6 /rGO [22], PbGeO 3 /graphene [23], as well as Fe 2 GeO 4 /rGO hybrids [24] have repeatedly confirmed that graphene possessed the capability of improving reversible capacity and cycling stability of the corresponding electrodes.…”
Section: A N U S C R I P Tmentioning
confidence: 99%